Student learning discipline: Problem and solution in online learning - Rahmat Aziz; Esa Nur Wahyuni; nur Hasib Muhammad; Achmad Ainur Ridlo; Mohamad Fahri Salam (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
Learning activities to develop students' character learning discipline at the junior high school level has given rise to difficulties for teachers and students. The paper aims to describe the form of student learning discipline behavior and analyze the role of teachers and principals during the learning process. The article is based on data collected from the results of the spread of open questionnaires to 30 students in three schools in East Java province. In addition, the research data was also obtained through interviews with 12 teachers and two principals. The results showed that principals and teachers have a significant role in determining the success of online learning. The principal's role in making flexible policies has been a determinant of the success of online learning. Likewise, the positive attitude of teachers towards students has contributed to the successful development of student learning disciplines. The paper suggests the need for more in-depth data retrieval methods to understand cases better.